Меlnychenko O.A., Yemchenko V.І. Priorities of public administration of dental services market development - Gryshyna, Nataliia (Pressing Problems of Public Administration, 2019)
The list of public administration subjects in the dental services market has been speci ed. Priorities of the public administration of the market development have been identi ed and separated in a broad sense and with regard to its individual subjects.